2017
DOI: 10.3390/ijerph14020160
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of a Vegetation Barrier and Resulting Impacts on Near-Highway Particle Number and Black Carbon Concentrations on a School Campus

Abstract: Traffic-related air pollution is a persistent concern especially in urban areas where populations live in close proximity to roadways. Innovative solutions are needed to minimize human exposure and the installation of vegetative barriers shows potential as a method to reduce near-road concentrations. This study investigates the impact of an existing stand of deciduous and evergreen trees on near-road total particle number (PNC) and black carbon (BC) concentrations across three seasons. Measurements were taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Forests near major roads may slightly worsen air quality in terms of traffic-related NO 2 pollution, however for PM 2.5 pollution, no difference between open and vegetated areas was found and for coarse PM (>PM 2.5 ) and large PM (>PM 10 ), the air pollution concentration levels were lower in the forest than in open transects [19]. Finally, in one study, a significant decrease according to the distance from the traffic lane was observed for PM 10 ,PM 2.5 ,and black carbon (BC) concentrations [24], while in another study, it was concluded that only a decrease in BC concentrations occurred with increased distance from the road and a similar effect was not observed for PM pollution [23].…”
Section: Local-scale Studiesmentioning
confidence: 93%
See 4 more Smart Citations
“…Forests near major roads may slightly worsen air quality in terms of traffic-related NO 2 pollution, however for PM 2.5 pollution, no difference between open and vegetated areas was found and for coarse PM (>PM 2.5 ) and large PM (>PM 10 ), the air pollution concentration levels were lower in the forest than in open transects [19]. Finally, in one study, a significant decrease according to the distance from the traffic lane was observed for PM 10 ,PM 2.5 ,and black carbon (BC) concentrations [24], while in another study, it was concluded that only a decrease in BC concentrations occurred with increased distance from the road and a similar effect was not observed for PM pollution [23].…”
Section: Local-scale Studiesmentioning
confidence: 93%
“…On-site air quality measurements, also if coupled with field vegetation inventories, and data analysis [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] On-site air quality measurements or soil sampling, measurements of pollution removal by means of laboratory techniques, including instrumental analysis on plant samples (e.g., microscopic analysis, spectroscopy, gravimetry, gas exchange measurements, wind tunnel experiments on leaves or branches etc.) and data analysis [31][32][33][34][35] Measurements of pollution removal by means of laboratory techniques, including instrumental analysis on plant samples and data analysis [11][12][13] Estimates of pollution removal by vegetation or statistical analysis based on field plant inventories or remote sensing data and existing literature/databases or air quality data [60][61][62][63][64][65][66] Modelling Approaches…”
Section: Field Measurements And/or Laboratory Analysismentioning
confidence: 99%
See 3 more Smart Citations